The Effect Of Profitability, Level Of Industry Type, Company Size, And Public Ownership On Sustainability Report Disclosure Of Companies Listed On Idx 2022 - Brigitta Febriani; Sukoharsono, Eko Ganis (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This research aims to find out the factors that influence the disclosure of sustainability reports, specifically profitability, type of industry, company size, and public share ownership. This research is quantitative research using secondary data in the form of sustainability reports of companies listed on the Indonesia Stock Exchange (IDX) for the reporting year 2022, prepared in accordance with GRI Standards. Samples were taken using purposive sampling technique with a total sample of 97 samples. This research was analyzed using multiple linear regression analysis to determine the effect of the independent variable on the dependent variable. The results of this research are profitability, level of industry type, company size, and public ownership determine Sustainability Report disclosure. Companies with higher profitability, larger company size, and a larger portion of public share ownership will increase the disclosure of corporate sustainability information as a form of responsibility to stakeholders. Companies with high profile level of industrial type have the risk of causing environmental damage and affecting society results in increasing level of sustainability report disclosure to gain public legitimacy